Physico-chemical characteristics of Rhizopus sp.-fermented fish feed pellets containing black soldier fly larvae (Hermetia illucens) meal. Issue 1 (April 2021) - Hariyono, C M; Yunianta; Harijono; Sriherwanto, C; Suja'i, I; Nadaviana, A; Junaedi, H; Ma'hadah, R; Komarudin
Abstract: In aquaculture, feed cost contributes the highest share in the total production cost. The increase in fishmeal price and the high cost of commercial fish feeds have prompted the search for alternatives. Thus, considerable research has been carried out to develop a farm-made feed that requires simpler methods and cheaper production costs. This study aimed at developing farm-made fish feed using simple equipment, locally available materials, and inexpensive fungal-based bio-floating technique. A combination of using black soldier fly ( Hermetia illucens ) larvae meal as a fishmeal replacement and Rhizopus sp. fermentation to provide floatability was used. An experiment using three different Rhizopus sp. inoculum doses (1, 2, and 3% w/w) and 3 different fermentation duration (30, 40, and 50 h) were designed, with unfermented feed as control. Results showed that fermented floating feeds gained better nutritional value and physical characteristics (p<0.05). The optimized treatment resulted in a fermented feed with the protein content of 29.72%; fibre 12.13%; fat 26.57%; and ash 7.83%. Relative to the unfermented control, all of the fermentation treatments produced feeds with high average values of floating ability (83.33%) and water stability (92.38).